Polyphenols as Plant-Based Nutraceuticals: Health Effects, Encapsulation, Nano-Delivery, and Application - Zhang, Zhiheng; Li, Xiaojing; Sang, Shangyuan; McClements, David Julian; Chen, Long; Long, Jie; Jiao, Aiquan; Jin, Zhengyu; Qiu, Chao (Foods, 2022)
Plant polyphenols have attracted considerable attention because of their key roles in preventing many diseases, including high blood sugar, high cholesterol, and cancer. A variety of functional foods have been designed and developed with plant polyphenols as the main active ingredients. Polyphenols mainly come from vegetables and fruits and can generally be divided according to their structure into flavonoids, astragalus, phenolic acids, and lignans. Polyphenols are a group of plant-derived functional food ingredients with different molecular structures and various biological activities including antioxidant, anti-inflammatory, and anticancer properties. However, many polyphenolic compounds have low oral bioavailability, which limits the application of polyphenols in nutraceuticals. Fortunately, green bio-based nanocarriers are well suited for encapsulating, protecting, and delivering polyphenols, thereby improving their bioavailability. In this paper, the health benefits of plant polyphenols in the prevention of various diseases are summarized, with a review of the research progress into bio-based nanocarriers for the improvement of the oral bioavailability of polyphenols. Polyphenols have great potential for application as key formulations in health and nutrition products. In the future, the development of food-grade delivery carriers for the encapsulation and delivery of polyphenolic compounds could well solve the limitations of poor water solubility and low bioavailability of polyphenols for practical applications.